TASAWUF SEBAGAI REVOLUSI SPIRITUAL DAN SOSIAL BAGI KEHIDUPAN MASYARAKAT ERA DISRUPSI - Muhamad Basyrul Muvid (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2021)
This article examines and analyzes the role of Sufism as a spiritual and moral revolution. Nowadays, in the era of disruption as an era in which all information can be accessed easily.Â People are experiencing spiritual and social crisis due to the massive use of media and social changing. The method used in this article is the study of literature, which examines and examines various documents, literature, articles, books and other references related to this theme. Results: First, that Sufism has a role to lead people to focus on themselves and find peace with God. At the same time, Sufism also lead people to be able to perform both their duty as the creature of God (habl min Allah) and as representatives of God (habl min an nas). Second, Sufism is also a social movement. It teaches people to build good relationships with the community and requires people to be active, optimistic and have social sensitivity